Evaluation of Traditional Medicines for Neurodegenerative Diseases Using Drosophila Models. - Lee, S.; Bang, S.M.; Lee, J.W.; Cho, K.S. (Evidence-based complementary and alternative medicine : eCAM, 2014)
Drosophila is one of the oldest and most powerful genetic models and has led to novel insights into a variety of biological processes. Recently, Drosophila has emerged as a model system to study human diseases, including several important neurodegenerative diseases. Because of the genomic similarity between Drosophila and humans, Drosophila neurodegenerative disease models exhibit a variety of human-disease-like phenotypes, facilitating fast and cost-effective in vivo genetic modifier screening and drug evaluation. Using these models, many disease-associated genetic factors have been identified, leading to the identification of compelling drug candidates. Recently, the safety and efficacy of traditional medicines for human diseases have been evaluated in various animal disease models. Despite the advantages of the Drosophila model, its usage in the evaluation of traditional medicines is only nascent. Here, we introduce the Drosophila model for neurodegenerative diseases and some examples demonstrating the successful application of Drosophila models in the evaluation of traditional medicines.